HUBUNGAN LINGKUNGAN BISNIS INTERNAL, INOVASI DAN KINERJA BISNIS PADA PENGEMBANG PERUMAHAN DI SULAWESI SELATAN - Nur Naninsih (Jurnal Bisnis dan Kewirausahaan, 2017)
The housing sector has evolved as the needs of the increasing community will be a place to live. Likewise, the growth in the need for decent shelter in Makassar creates a huge housing market potential, as evidenced by the rising construction of new residential areas. The purpose of research to analyze the internal business environment and innovation partially and simultan affect the business performance, and to analyze the internal business environment most dominant influence on business performance. Data were collected by 45 respondents. Processing data using SPSS version 16, which includes validity using factor analysis, reliability testing using Cronbach Alpha techniques and hypothesis testing includes testing the feasibility of the model (R Square test), t-test. Based on the statistical analysis that has been done, it appears that the F test hasith shows that Fhitug = 5.306> from Ftabel = 1.671. This shows that together independent variables have a significant influence on the dependent variable. This means that the internal business environment (X1), and innovation (X2) variables simultaneously have an effect on the improvement of business performance on Housing Developers in South Sulawesi. It is known that the value of Adjasted R square = 0.453 which is the index of determination states the percentage of about 45.3% improvement in business performance of Housing Developers In South Sulawesi can be explained by these two variables, while the remaining 54.2% is explained by other causes that do not become research variables. The most dominant variable of influence is the internal business environment variable (X1).